Islamic State’s Online Activity and Responses - Stuart Macdonald (CRC Press, 2019)
This book examines Islamic State’s online activity at the peak of its "golden age" between 2014 and 2017 and evaluates some of the principal responses to this phenomenon.Featuring contributions from experts across a range of disciplines, the volume examines a variety of aspects of IS’s online activity, including their strategic objectives, the content and nature of their magazines and videos, and their online targeting of females and depiction of children. It also details and analyses responses to IS’s online activity – from content moderation and account suspensions to informal counter-messaging and disrupting terrorist financing – and explores the possible impact of technological developments, such as decentralised and peer-to-peer networks, going forward. Platforms discussed include dedicated jihadi forums, major social media sites such as Facebook, Twitter, and YouTube, and newer services, including Twister.